Assessing oestrogenic effects of brominated flame retardants hexabromocyclododecane and tetrabromobisphenol A on MCF-7 cells - Dorosh, A; Děd, Lukáš; Elzeinová, Fatima; Pěknicová, Jana (Folia biologica (Praha), 2011)
Tetrabromobisphenol A (TBBPA) is the main flame retardant used in printed circuit boards and laminates. The human population is highly exposed to TBBPA as it is used in consumer electronics as well as office and communication equipment. The main use of hexabromocyclododecane (HBCD) is in insulation foam boards, which are widely used in the construction sector. Brominated flame retardants may possess endocrine disrupting activity and thus represent a threat to the environment, including humans and their reproduction. The aim of this work was to evaluate the oestrogenic effects of TBBPA and HBCD in vitro on MCF-7 cells. We used the proliferation test (E-screen assay) in MCF-7 breast cancer cells and reverse transcription quantitative polymerase chain reaction analysis of TFF1 gene expression to analyse oestrogenicity of the studied compounds. RT-qPCR has proved to be a fast and valuable molecular technique in gene expression quantification. HBCD but not TBBPA increased cell proliferation in MCF-7 cells and up-regulated TFF1 gene expression in a concentration-dependent manner. Anti-oestrogen ICI 182,780 inhibited up-regulation of TFF1 by HBCD. We have shown that HBCD displays oestrogen- like effects on MCF-7 cells. TBBPA, on the other hand, has not shown any oestrogenic effect mediated by the oestrogen receptor ?.
Keywords: Up-Regulation; retardanty hoření; Reverse Transcriptase Polymerase Chain Reaction; Cell Proliferation; Humans; Tumor Suppressor Proteins; nádorové buněčné linie; nádorové supresorové proteiny; Endocrine Disruptors; Financing, Organized; Flame Retardants; Estrogen Antagonists; financování organizované; Estrogens; Hydrocarbons, Brominated; estrogeny; proliferace buněk; bromované uhlovodíky; polymerázová řetězová reakce s reverzní transkripcí; Polybrominated Biphenyls; Estriol; Estrogen Receptor alpha; alfa receptor estrogenů; polybrombifenylové sloučeniny; estriol; upregulace; Gene Expression; antagonisté estrogenu; lidé; Cell Line, Tumor; exprese genu; endokrinní disruptory